PENGARUH KOMPETENSI, KOMITMEN KARYAWAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI PDAM KOTA SURABAYA DENGAN KOMUNIKASI SEBAGAI VARIABEL INTERVENING - jurnalmap map; Tiara Dinar Aulia; Indra Prasetyo; Subijanto ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2018)
ABSTRACT This study aims to describe competence, employee commitment and work motivation towards the performance of PDAM Kota Surabaya employees, knowing the significant direct effect of competence, employee commitment, and motivation on employee communication and on employee performance, knowing the indirect influence of competence, employee commitment, and motivation through communication with the performance of PDAM Kota Surabaya employees. The population in the study were all employees of PDAM Kota Surabaya, amounting to 67 employees. The quantitative descriptive analysis approach and inferential quantitative analysis and path analysis (path analysis) with competence, commitment and motivation as independent variables, communication as intervening variables, and performance as the dependent variable. The results of the data analysis show that competency, commitment, motivation, communication and employee performance are in good condition. Competence, commitment, motivation and communication partially or simultaneously have a significant direct effect on employee performance. Competence, commitment and motivation have an indirect effect on performance through communication variables. From the variables of competence, commitment, motivation and communication, the dominant influence on performance is the communication variable. Keywords: competence, commitment, motivation, communication, performance